Integration Of Leverage Mediation With Internal Audit Compliance and Determination of Corporate Tax Avoidance Mechanisms - Riyani, Etik Ipda; Prasetiyo, Yudhi; Pradana, Novta Winkey (Dinamika Akuntansi Keuangan dan Perbankan, 2026)
This study aims to examine the factors influencing tax avoidance, with debt (leverage) acting as a mediating variable. The independent variables include internal audit compliance, sales level, capital intensity, firm political connections, and corporate social responsibility (CSR). The sample consists of 306 manufacturing firms from the consumer goods, basic materials, and industrial sub-sectors listed on the Indonesian Stock Exchange during the 2019–2021 period, selected using purposive sampling.The study employs multiple linear regression and robust regression to compare results across each year of observation. The findings indicate that capital intensity and political connections of the board of directors have a significant effect on tax avoidance, particularly when leverage (Debt to Asset Ratio) serves as a mediating variable. This suggests that firms with high capital intensity and strong political connections tend to use debt strategically to reduce their tax burden. In contrast, internal audit compliance, political connections of the board of commissioners, and sales levels do not show a significant impact on tax avoidance under either regression method. Overall, the results highlight the importance of monitoring leverage usage and political connections to prevent excessive tax avoidance practices.